Comparative Analysis Of Donor Site Morbidity and Rates Of Seroma Formation In Extended Versus Muscle-Only Latissimus Dorsi Flaps - Masud, Rafia; Rashid, Mamood; Sarwar, Saad Ur Rehman; Khan, Muhammad Ibrahim; Mohmand, Shahrukh; Askari, Fatima (Journal of Rawalpindi Medical College, 2025)
Objective: To compare the incidence of seroma formation and donor site morbidity between Extended Latissimus Dorsi (ELD) flaps and muscle-only Latissimus Dorsi (MLD) flaps in reconstructive surgery. Methods: A comparative cross-sectional study was conducted at the Department of Plastic Surgery, Shifa International Hospital, Islamabad. A total of 60 patients undergoing breast reconstruction, upper and lower limb reconstruction after tumor resections or trauma and functional muscle transfers in brachial plexus injuries with either ELD (n=30) or muscle-only LD (n=30) flaps were included. Data on demographics, comorbidities and postoperative complications such as seroma formation, wound infection, skin necrosis, dehiscence, and pain (VAS) were collected over a 3-month follow-up period. Statistical analysis was performed using SPSS version 26.0, with significance set at p<0.05. Results: Seroma formation was significantly higher in the ELD group (43.33%) compared to the MLD group (10%) (p<0.001), with a greater mean seroma volume (97.7 ± 38.5 ml vs. 25.2 ± 12.1 ml). Pain scores on Day 1 and at 1 month were also significantly higher in the ELD group (p<0.01). Other complications—wound infection, skin necrosis, and dehiscence—were more frequent in the ELD group but not statistically significant. Seroma recurrence was also more prevalent in the ELD group. Conclusion: The ELD flap has been associated with significantly higher donor site morbidity, particularly seroma formation and postoperative pain, when compared to the muscle-only LD flap. These results indicate that ELD flaps can yield increased tissue volume with increased risk of complications and warrant careful consideration to improve operative techniques